Wireless and Wearable Real-time Health Monitoring Systems: A Review of Recent Developments - Bhavna Pawar; Pornima Choulwar; Pooja Mule (International Journal of Radio Frequency Innovations, 2024)
This paper explores the interdependent relationship between mental and physical health, highlighting the impact of stress and anxiety on the body by introducing an innovative Real- Time Health Monitoring System. This system monitors both mental well-being and physical health using advanced physical health sensors and Facial Emotion Recognition (FER) technology. Leveraging high-precision sensors such as Temperature and pulse oximeters, it continuously monitors vital physiological parameters such as Body Temperature and Pulse Rate (SpO2) in real time. Simultaneously, a FER-based Deep Learning model captures and analyzes emotional states, ranging from happiness to anxiety and everything in between. Processed by an ESP32 microcontroller, the data is seamlessly acquired, graphically displayed, and stored on a Cloud Platform, allowing for in-depth analysis. Quantitative data has been used to analyze patterns and relationships between emotional states and health parameters for deeper understanding of the mind-body connection. The results demonstrate the real-time monitoring of an individual's emotional state and its impact on vital health parameters, such as Temperature and Pulse Rate. In conclusion, our findings highlight the importance of integrating mental health into physical health and the potential impact of cutting-edge technologies on healthcare management by providing a holistic understanding of each person's well-being.
Keywords: : Real-time health monitoring; body temperature; facial emotion recognition (FER); mind-body connection; pulse oximeter (SPO2)